Evaluating PAX1/JAM3 methylation for triage in HPV 16/18-infected women - Jing Fei; Lingyun Zhai; Jing Wang; Xiaoqing Zhu; Pei Liu; Linhai Wang; Dongxue Ma; Lei Li; Jianwei Zhou (Clinical Epigenetics)
Abstract Objective Referring all women who tested positive for human papillomavirus (HPV) 16/18 to colposcopy may lead to potential over-referral issues. Triage tests based on cytology results face challenges in achieving accurate diagnoses. Our study aims to assess the clinical effectiveness of PAX1/JAM3 methylation (CISCER) test as a triage method for HPV 16/18-positive women. Methods From November 2021 to December 2022, a total of 334 women who tested positive for HPV 16/18 and were referred to colposcopy at The Second Affiliated Hospital of Zhejiang University School of Medicine were studied. The clinical utility of the CISCER test, cytology, and the combination of CISCER with cytology as potential triage tests was compared. Results We observed a significant increase in the methylation levels of PAX1 gene and JAM3 gene in women with cervical intraepithelial neoplasia (CIN) grade 2 or severe (CIN2+). The CISCER test demonstrated superior triage performance over cytology, even when used in combination with cytology, showing a high sensitivity of 89.0% (95% confidence interval [CI] 82.9–95.1%) and specificity of 95.3% (95% CI 92.6–98.0%). It achieved an area under the curve of 0.921 (95% CI 0.877–0.966) and an odds ratio of 164.02 (95% CI 68.64–391.95). The immediate CIN2+ risk based on positive CISCER results would be 89.0% (95% CI 80.8–94.1%), with an estimated average of 1.12 referrals needed to detect one CIN2+ case. Moreover, CISCER triaging successfully identified all cancer patients and did not miss any CIN3+ cases among women aged ≥ 30. Conclusions The PAX1/JAM3 methylation detection exhibited excellent accuracy in identifying cervical precancerous lesions in HPV 16/18-positive women and could be considered as a triage tool to reduce excessive referrals for colposcopy and overtreatment.